Implikasi Pariwisata di Makam Dr. IL. Nomensen Sigumpar Sebagai Daya Tarik Wisata - Ricki Cristian Manalu; Liyus Waruwu; Bambang T.J. Hutagalung; Tio R.J. Nadeak; Yulia K. S. Sitepu (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
The purpose of this study was to determine of implications the tourism at Makam II. Nommensen in Sigumpar. Implication is the impact or result caused by one thing, which in this case means the impact obtained from tourism the IL.Nommensen tomb. This research uses a qualitative method with a descriptive approach and data collection techniques through the results of observations, interviews, and documentation of several informants, namely the West Sigumpar Village Government, Tourism Managers, and Village Communities, as well as the Toba Culture and Tourism Office. With the member of informants five people. Through the results of the research that has been done, the researchers describe that IL. Nommensen is an interesting tour with a spiritual aspect so that many tourists visit on holidays, but some of the impacts of tourist visits have not been felt by related parties such as managers, the Tourism Office, especially from the community. Especially the economic impact which is expected to increase the local economy but the results of the economic impact are still not felt by related parties. Therefore, researchers recommend analyzing the implications of the tourist attraction so that later when there is improvement, the most important impact is not forgotten to be associated with the sustainability of tourism. Thus the cooperation of the parties involved is needed so that the impact of the IL Tomb tourist attraction. Nommensen can be felt by the community, managers, and the government.